2006
DOI: 10.1103/physrevlett.96.247201
|View full text |Cite
|
Sign up to set email alerts
|

Spin Waves in the Frustrated Kagomé Lattice AntiferromagnetKFe3(OH)6(SO4)2

Abstract: The spin wave excitations of the S=5/2 kagomé lattice antiferromagnet KFe3(OH)6(SO4)2 have been measured using high-resolution inelastic neutron scattering. We directly observe a flat mode which corresponds to a lifted "zero energy mode," verifying a fundamental prediction for the kagomé lattice. A simple Heisenberg spin Hamiltonian provides an excellent fit to our spin wave data. The antisymmetric Dzyaloshinskii-Moriya interaction is the primary source of anisotropy and explains the low-temperature magnetizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
179
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 26 publications
12
179
1
Order By: Relevance
“…The crystal structure of the -phase has been identified as rhombohedral c R3 in [28], tetragonal in [29], cubic mcm I / 4 m Pm3 in [30], monoclinic m P 1 2 or m C 2 in [31], and, recently, as orthorhombic Pbnm in [32]. The change of structure, loss of magnetic order and metallization of BiFeO 3 are also observed under pressure of [45][46][47][48][49][50][51][52][53][54][55] GPa at room temperature [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the -phase has been identified as rhombohedral c R3 in [28], tetragonal in [29], cubic mcm I / 4 m Pm3 in [30], monoclinic m P 1 2 or m C 2 in [31], and, recently, as orthorhombic Pbnm in [32]. The change of structure, loss of magnetic order and metallization of BiFeO 3 are also observed under pressure of [45][46][47][48][49][50][51][52][53][54][55] GPa at room temperature [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the DMI suppresses the QSL phase of frustrated kagomé antiferromagnets up to a critical value [30]. The syntheses of materials have shown that various experimentally accessible frustrated kagomé antiferromagnets show evidence of coplanar/noncollinear q = 0 LRO at specific temperatures [29][30][31][32][33][34] [36] are fragile in the presence of applied magnetic field or pressure and they show evidence of LRO [37,38]. However, the role of DMI and magnetic field in frustrated kagome magnets has not been investigated in the context of thermal Hall effect and topological spin excitations.…”
mentioning
confidence: 99%
“…Unfortunately, no especially good model system for experimental studies exists. Considerable investigations were made of jarosite minerals [150][151][152][153], and recently materials based on the langasite structure have appeared [154]. For the S = 1/2 system, the most promising experimental realizations are again provided by natural or synthetic mineral samples based on the clinoatacamite structure [155].…”
Section: Kagome Spin Liquidsmentioning
confidence: 99%